‘I Just Wanted to Get it Over and Done With’: a grounded theory of psychological need frustration in video games - Ballou,N; Deterding,S (Association for Computing Machinery (ACM), 2023)
Psychological need frustration—experiences like failure, loneliness, or coercion—is emerging as a promising explanation for why people disengage with games and other entertainment media, and how media may induce dysregulated use and ill-being. However, existing research on game-related need frustration relies on general instruments with unclear content validity for games. We also do not know how need frustration arises in video games, nor how it leads to disengagement. We therefore conducted a semi-structured interview study with 12 video game players, following grounded theory methods to develop a model of need-frustrating play. We find that need frustration is a common and impactful experience in games, with distinct antecedents not fully captured in existing measures. Felt need frustration arises when observed need-frustrating events negatively violate expected need frustration or satisfaction; repeated violations update players’ expectations, which lead them to modulate or quit play to reduce expected frustration exposure.